2016
DOI: 10.1111/tid.12555
|View full text |Cite
|
Sign up to set email alerts
|

Risk of tuberculosis after lung transplantation: the value of pretransplant chest computed tomography and the impact of mTOR inhibitors and azathioprine use

Abstract: Residual lesions in the pretransplant chest CTs and the use of azathioprine and mTOR inhibitors are associated with the risk of TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…We studied 398 consecutive lung transplant patients. 6 Of these, 92 (24.9%) had LTBI: 70 confirmed by a positive TST and the remaining 22 by radiological abnormalities compatible with residual TB on the pretransplant chest CT scan despite having a negative TST. After discussing treatment options with the patients, a 3HR treatment regimen was initiated in 22 patients with LTBI (23.9%) and in another patient because he had a history of previous incomplete treatment for active TB (23 patients altogether; Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We studied 398 consecutive lung transplant patients. 6 Of these, 92 (24.9%) had LTBI: 70 confirmed by a positive TST and the remaining 22 by radiological abnormalities compatible with residual TB on the pretransplant chest CT scan despite having a negative TST. After discussing treatment options with the patients, a 3HR treatment regimen was initiated in 22 patients with LTBI (23.9%) and in another patient because he had a history of previous incomplete treatment for active TB (23 patients altogether; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We studied 398 consecutive lung transplant patients . Of these, 92 (24.9%) had LTBI: 70 confirmed by a positive TST and the remaining 22 by radiological abnormalities compatible with residual TB on the pretransplant chest CT scan despite having a negative TST.…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis included a total of 7811 participants, including 1361 with positive Characteristics of included studies are shown in Table 1. Ten studies were conducted in kidney transplantation, [15][16][17][18][19][20][21][22][23][24][25] nine in liver transplantation, [26][27][28][29][30][31][32][33][34] one in lung transplantation, 35 and four in mixed populations of solid organ transplantation. [36][37][38][39] Twelve studies compared the odds of a positive IGRAs and TST in candidates/recipients with or without risk factors, whereas nine studies compared TST alone and three studies compared IGRAs alone.…”
Section: Studies Identifiedmentioning
confidence: 99%
“…QuantiFERON ® -TB Gold-based pre-transplant screening performance and active TB post transplant' by Hand et al 1 The authors' results are in accordance with our previously published data in lung transplantation, in which we reported that radiologic findings in pre-transplant chest computed tomography (CT) compatible with residual TB are an independent risk factor for post-transplant TB. 2 Tuberculin skin test (TST) and interferon gamma release assays (IGRA) are the current available tests to evaluate a latent TB infection (LTBI), but these tests do not have a good positive predictive value for post-transplant TB in solid organ recipients. In the RESITRA cohort, 4388 multiple solid organ transplant patients were included, and age and lung transplantation were the only two independent risk factors for post-transplant TB in the multivariate analysis.…”
Section: Tuberculin Skin Test Interferon Gamma Release Assays or Jusmentioning
confidence: 99%
“…3 In a previous study, we conducted with 398 lung transplant recipients, TST was not found to be a risk factor either. 2 As the first step to evaluate a LTBI, we propose examining chest xray/CT scans to search for radiologic findings of untreated or healed TB (apical fibro-nodular lesions, calcified solitary nodules, calcified lymph nodes, or pleural thickening). In patients from countries with a high TB burden, a chest CT could provide additional information.…”
Section: Tuberculin Skin Test Interferon Gamma Release Assays or Jusmentioning
confidence: 99%